Optimization of the enzymatic synthesis of pentyl oleate with lipase immobilized onto novel structured support - Cavallaro, Valeria (2019)
The term biorefinery is related to the sustainable production of value-added bioproducts and bioenergy from biomass. Esters from fatty acids are important compounds synthesized from by-products of the oleochemical industry. In agreement with the biorefinery concept, it is important to search for catalysts that reduce the consumption of energy and water, using moderate operation conditions and low reaction times. In this work, response surface methodology (RSM) was used to optimize the enzymatic synthesis of pentyl oleate using Candida antarctica lipase B (CALB) immobilized on a polyethylene-aluminum structured support. A factorial design was employed to evaluate the effects of several parameters on the ester yield. To obtain a model with a good fit, an approach to reaction mechanism and enzyme kinetics was taken into consideration. Experimental findings were correlated and explained using equations of a ping-pong bi-bi kinetic model and considering the inhibitory effects of both substrates. The developed model was consistent with the experimental data predicting an increase in pentyl oleate production with increasing temperature and a decrease with higher oleic acid amounts and alcohol to acid molar ratios. This model could be useful in a future industrial application of CALB/LLDPE/Al to minimize the costs in oleochemical biorefineries.